Dual - Value Dynamics in Street Coffee Consumption: The Mediating Role of Customer Engagement Between Perceived Price Fairness and Social Experience Toward Repurchase Intention - Elfina O.P Damanik; Johanes Wilfrid Pagihutan Purba; Hengki Mangiring Parulian Simarmata; Darwin Lie; Nagian Toni (Fakultas Ekonomi Universitas Simalungun, 2025)
This study examines how perceived price fairness and consumer social experience affect customer engagement and repurchase intention among street coffee consumers in Indonesia. Using a quantitative explanatory approach with Partial Least Squares Structural Equation Modeling (PLS-SEM) on data from 400 respondents, the research identifies a dual-value dynamic between economic fairness and social experience in shaping consumer loyalty. The findings show that price fairness does not significantly influence engagement but directly increases repurchase intention, indicating that transparent pricing builds rational trust and behavioral loyalty. In contrast, consumer social experience strongly enhances both engagement and repurchase intention, confirming that emotional connection and social belonging are the main drivers of repeat behavior. Customer engagement also significantly predicts repurchase intention and mediates the relationship between social experience and loyalty, while its mediating effect between price fairness and loyalty is insignificant. These results demonstrate that engagement functions as a psychological bridge between social interaction and behavioral commitment. The study contributes to understanding consumer loyalty in informal markets and suggests that entrepreneurs should combine fair pricing with interactive, community-based experiences to strengthen customer trust and long-term loyalty.